2018
DOI: 10.1159/000494602
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of miR-195-5p/MMP14 on Proliferation and Invasion of Cervical Carcinoma Cells Through TNF Signaling Pathway Based on Bioinformatics Analysis of Microarray Profiling

Abstract: Background/Aims: This study is aimed at identification of miR-195-5p/MMP14 expression in cervical cancer (CC) and their roles on cell proliferation and invasion profile of CC cells through TNF signaling pathway in CC. Methods: Microarray analysis, gene set enrichment analysis (GSEA) and DAVID were used to analyze differentially expressed miRNAs, mRNAs and signaling pathways. MiR-195-5p and MMP14 expression levels in CC cell were determined by qRT-PCR. Western blot was employed to measure MMP14 and TNF signalin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 23 publications
0
34
0
2
Order By: Relevance
“…miRNAs represent endogenous non-protein-coding small noncoding RNAs, 18-25 nucleotides in length, that have been implicated in a wide array of tumor cell physiological processes including cell proliferation, invasion, apoptosis, and self-renewal by interacting with their specific target genes (Wang et al, Abbreviations: 3 UTR, 3 untranslated region; AGAP2-AS1, AGAP2 antisense RNA 1; Ago2, Argonaute 2; ANOVA, analysis of variance; BCA, bicinchoninic acid; BPH, benign prostatic hyperplasia; BSA, bovine serum albumin; CCK-8, cell counting kit-8; cDNA, complementary DNA; ceRNAs, competing endogenous RNAs; DAB, diaminobenzidine; DMEM, Dulbecco's modified Eagle's medium; DTT, dithiothreitol; ECL, enhanced chemiluminescence; EDTA, ethylene diamine tetraacetic acid; FBS, fetal bovine serum; GEO, Gene Expression Omnibus; IgG, immunoglobulin G; ISUP, International Society of Urological Pathology; lncRNAs, long non-coding RNAs;; miRNAs/miRs, microRNAs; MMP2, matrix metalloproteinase 2; mut, mutant; NC, negative control; NSCLC, non-small cell lung cancer; OD, optical density; Opti-MEM, Opti-minimum essential medium; PBS, phosphate buffered saline; PCA3, prostate cancer antigen 3; PCAT1, prostate cancer associated ncRNA transcript 1; PCGEM1, prostate cancer gene expression marker 1; PEI, polyethylenimine; PRR11, proline-rich protein 11; RAID, redundant arrays of inexpensive disks; RIP, RNA-binding protein immunoprecipitation; RIPA, radioimmunoprecipitation assay; RPMI, Roswell Park Memorial Institute; RT-qPCR, Reverse transcription quantitative polymerase chain reaction; siRNA, small interfering RNA; SP, streptavidin-perosidase; SPF, specific pathogen-free; SPSS, Statistical Product and Service Solutions; wt, wild type. 2017; Li et al, 2018). Furthermore, accumulating evidence has suggested that miRNAs play a crucial role in regulating tumor development (Ling et al, 2013;Rupaimoole and Slack, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs represent endogenous non-protein-coding small noncoding RNAs, 18-25 nucleotides in length, that have been implicated in a wide array of tumor cell physiological processes including cell proliferation, invasion, apoptosis, and self-renewal by interacting with their specific target genes (Wang et al, Abbreviations: 3 UTR, 3 untranslated region; AGAP2-AS1, AGAP2 antisense RNA 1; Ago2, Argonaute 2; ANOVA, analysis of variance; BCA, bicinchoninic acid; BPH, benign prostatic hyperplasia; BSA, bovine serum albumin; CCK-8, cell counting kit-8; cDNA, complementary DNA; ceRNAs, competing endogenous RNAs; DAB, diaminobenzidine; DMEM, Dulbecco's modified Eagle's medium; DTT, dithiothreitol; ECL, enhanced chemiluminescence; EDTA, ethylene diamine tetraacetic acid; FBS, fetal bovine serum; GEO, Gene Expression Omnibus; IgG, immunoglobulin G; ISUP, International Society of Urological Pathology; lncRNAs, long non-coding RNAs;; miRNAs/miRs, microRNAs; MMP2, matrix metalloproteinase 2; mut, mutant; NC, negative control; NSCLC, non-small cell lung cancer; OD, optical density; Opti-MEM, Opti-minimum essential medium; PBS, phosphate buffered saline; PCA3, prostate cancer antigen 3; PCAT1, prostate cancer associated ncRNA transcript 1; PCGEM1, prostate cancer gene expression marker 1; PEI, polyethylenimine; PRR11, proline-rich protein 11; RAID, redundant arrays of inexpensive disks; RIP, RNA-binding protein immunoprecipitation; RIPA, radioimmunoprecipitation assay; RPMI, Roswell Park Memorial Institute; RT-qPCR, Reverse transcription quantitative polymerase chain reaction; siRNA, small interfering RNA; SP, streptavidin-perosidase; SPF, specific pathogen-free; SPSS, Statistical Product and Service Solutions; wt, wild type. 2017; Li et al, 2018). Furthermore, accumulating evidence has suggested that miRNAs play a crucial role in regulating tumor development (Ling et al, 2013;Rupaimoole and Slack, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Fernando et al suggested NOD-like Receptors as important players and targets in the interface between innate immunity and cancer [35]. Previous study found that TNF signaling pathway was involved in the regulation of proliferation and invasion in cervical carcinoma [36]. Single-stranded DNA-binding proteins are supposed as the key of the integrity of the genome [37].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are reported to serve as diagnostic or prognostic biomarkers in various cancers [28,29]. Furthermore, miRNAs can be detected accurately by various techniques, such as nextgeneration sequencing, microarray and qRT-PCR [ 30,31], among others. The discovery of miRNAs has provided novel insight into the molecular mechanisms and treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%